2021
DOI: 10.1002/chem.202102574
|View full text |Cite
|
Sign up to set email alerts
|

Structure‐Based Design, Synthesis, and Biological Evaluation of Hsp90β‐Selective Inhibitors

Abstract: The 90 kDa heat shock proteins (Hsp90) are molecular chaperones that are responsible for the folding and/or trafficking of ~400 client proteins, many of which are directly associated with cancer progression. Consequently, inhibition of Hsp90 can exhibit similar activity as combination therapy as multiple signaling nodes can be targeted simultaneously. In fact, seventeen small-molecule inhibitors that bind the Hsp90 N-terminus entered clinical trials for the treatment of cancer, all of which exhibited pan-inhib… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
7
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 10 publications
(7 citation statements)
references
References 44 publications
(93 reference statements)
0
7
0
Order By: Relevance
“…Additionally, novel approaches for Hsp90 targeted therapy intend to avoid harmful side effects associated with pan-inhibition by using non-traditional modulation of Hsp90, including C-terminal inhibition or isoform-selective inhibition. The research group of Blagg has recently made a major contribution to this research area by developing several new isoform-selective inhibitors (Chaudhury et al 2021 ; Crowley et al 2017 , 2016 ; Khandelwal et al 2018 , 2017 ; Mishra et al 2021a , 2021b , 2017 ; Muth et al 2014 ), including the more challenging development of Hsp90α (Mishra et al 2021a ) and Hsp90β (Chaudhury et al 2021 ; Khandelwal et al 2018 ; Mishra et al 2021b ) selective compounds. Their Hsp90β-selective inhibitors were claimed to be cytotoxic to cancer cells while not inducing a HSR, thereby overcoming the detriments associated with pan-Hsp90 inhibition (Mishra et al 2021b ).…”
Section: Discussionmentioning
confidence: 99%
“…Additionally, novel approaches for Hsp90 targeted therapy intend to avoid harmful side effects associated with pan-inhibition by using non-traditional modulation of Hsp90, including C-terminal inhibition or isoform-selective inhibition. The research group of Blagg has recently made a major contribution to this research area by developing several new isoform-selective inhibitors (Chaudhury et al 2021 ; Crowley et al 2017 , 2016 ; Khandelwal et al 2018 , 2017 ; Mishra et al 2021a , 2021b , 2017 ; Muth et al 2014 ), including the more challenging development of Hsp90α (Mishra et al 2021a ) and Hsp90β (Chaudhury et al 2021 ; Khandelwal et al 2018 ; Mishra et al 2021b ) selective compounds. Their Hsp90β-selective inhibitors were claimed to be cytotoxic to cancer cells while not inducing a HSR, thereby overcoming the detriments associated with pan-Hsp90 inhibition (Mishra et al 2021b ).…”
Section: Discussionmentioning
confidence: 99%
“…So, the researches on isoform-selective inhibitors are still continually deepened, which is conductive to reducing the pan-inhibition of Hsp90. In the study of Chaudhury et al, the reported complex shows the greatest selectivity towards HSP90β, and even more than 370 fold compared with HSP90α [ 143 ]. In general, although the problems of targeting HSP90 in disease treatment have revealed, it still be a feasible approach because these problems could be gradually solved.…”
Section: Discussionmentioning
confidence: 99%
“…124 To date, a roster of over 400 known HSP90 client proteins has been assembled, most of which are oncogene products or key regulators of signal transduction pathways, significantly promoting the initiation and progression of cancer. 125 Furthermore, the progression of cancer heavily relies on essential signaling pathways, each prominently featuring key oncoproteins recognized as HSP90 clients (Figure 3). For instance, the signaling cascade of TGF-β plays a critical role in governing various cellular processes, including cell proliferation, differentiation, apoptosis, and migration.…”
Section: Roles Of Hsp90 and Its Co-chaperones In Cancermentioning
confidence: 99%